The Chemistry of Metal-Organic Frameworks: Synthesis, Characterization, and Applications 2016
DOI: 10.1002/9783527693078.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Group 3 Elements and Lanthanide Metals

Abstract: Scheme 9.1 Ln-MOFs and the multifunctionality of relevant properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 196 publications
0
6
0
Order By: Relevance
“…Compared to the transition metals more commonly applied for MOF synthesis, the design of Ln-MOFs is more complex due to the high and variable coordination numbers (CN) of the trivalent lanthanide ions. On the other hand, the flexible coordination geometry hampers the prediction and control of the synthesized Ln-MOF structures; however, on the other hand, it opens the option to synthesize unusual and new architectures. With the same lanthanide and organic linker, it is possible to realize distinct crystal structures . Since the pioneering synthesis by Reineke et al, Ln-MOF syntheses with BDC and derivatives reported structures crystallizing mostly in monoclinic and triclinic space groups.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the transition metals more commonly applied for MOF synthesis, the design of Ln-MOFs is more complex due to the high and variable coordination numbers (CN) of the trivalent lanthanide ions. On the other hand, the flexible coordination geometry hampers the prediction and control of the synthesized Ln-MOF structures; however, on the other hand, it opens the option to synthesize unusual and new architectures. With the same lanthanide and organic linker, it is possible to realize distinct crystal structures . Since the pioneering synthesis by Reineke et al, Ln-MOF syntheses with BDC and derivatives reported structures crystallizing mostly in monoclinic and triclinic space groups.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are crystalline materials that are formed by the linkage of inorganic and organic units via strong bonds resulting in porous structures . Based on the principles of reticular chemistry, MOFs are designed by the appropriate choice of inorganic and organic building units, with well-defined geometrical features, to produce structures with targeted topologies. , For those MOFs constructed from lanthanide-based inorganic clusters linked by multicarboxylic acid linkers, an extensive number of different three-dimensional (3D) networks have been reported . This is primarily due to the high variability in coordination environment of lanthanide cations.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily due to the high variability in coordination environment of lanthanide cations. The use of Ln-based building units in the construction of new MOFs is attractive though because Ln cations typically have a high density of coordinated solvent ligands, which, when removed, can produce unsaturated metal sites that serve as gas binding or Lewis acidic sites . Moreover, hydroxyl ligands derived from water molecules binding to metal clusters have been exploited for their Lewis and/or Brønsted acidity in catalytic reactions. , Therefore, lanthanide-based metal–organic frameworks (Ln-MOFs) are promising candidates for the applications of gas capture and heterogeneous acid-catalyzed reactions. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in high coordinative demand and brings out a high coordination number and connectivity, which facilitates the formation of stable 3D networks. 41 According to the best of our available knowledge, MOF-76(Y) was used for the very first time as filler in Matrimid polymer to fabricate MMMs. Gas permeation experiments under different conditions were conducted using pure and mixed gas compositions of CO 2 , CH 4 , and N 2 .…”
Section: Introductionmentioning
confidence: 99%